Composition and Physicochemical Properties of Pomace of Various Cultivars of Blackberry (Rubus fruticosus L.) - Indrė Čechovičienė; Alvyra Šlepetienė; Milda Gumbytė; Aurelija Paulauskienė; Živilė Tarasevičienė (Horticulturae, 2023)
The objective of this study is to assess the proximate chemical composition, and the physical and techno-functional properties of blackberry pomace from different cultivars (‘Polar’, ‘Orkan’, ‘Brzezina’). Blackberry pomace primarily comprises seeds and other parts, such as pulps/skins. It serves as a rich source of bioactive compounds, particularly anthocyanins, and demonstrates notable functional properties, including water holding capacity, oil holding capacity, swelling capacity, and various fiber fractions. Moreover, anthocyanin-rich fruits are interesting due to their health-promoting properties and intensive color. Total anthocyanin content (TAC) ranged from 113.82 mg 100 g−1 d.w. to 129.58 mg 100 g−1 d.w. in blackberry pomace. Fiber fractions, including ADF, NDF, lignin, and WSCs, exhibited significant variations among the different blackberry pomace cultivars as well as color.